Paeoniflorin Inhibits ASK1-TF Axis by Up-Regulating SOCS3 to Alleviate Radiation Enteritis - Sheng, Lei; Hu, Fan; Yu, Hanqing; Tao, Xueyou; Jia, Rumeng; Gu, Yufeng; Chen, Lu; Kong, Hong; Miao, Chen; Fei, Wenjing; Yang, Yang; Jia, Jinhui; et al. (Frontiers in Pharmacology, 2022)
Radiation enteritis is a major dose-limiting adverse reaction to radiotherapy for tumors, while the current clinical treatment is relatively limited. Intestinal vascular inflammation and damage are the core mechanisms of radiation enteritis and become a research highlight. Suppressor of cytokine signaling 3 (SOCS3) is an endogenous “inflammation brake” to inhibit the inflammatory response. We hypothesized that paeoniflorin, a pinane monoterpene bitter glycoside, could increase SOCS3 expression to improve enteritis and reduce the mortality of radiotherapy mice. Laser doppler flowmetry was used to detect the changes of intestinal blood flow in mice. RAW264.7 and HUVEC cells were used to investigate the pharmacological effects and the mechanism of radiation injury. Radiation induced the formation of intestinal inflammation and slow blood flow induced in mice. Paeoniflorin alleviated intestinal atrophy, prevented thrombosis, improved radiation enteritis and reduced mortality in radiotherapy mice. Paeoniflorin decreased the expression of p-ASK1 and tissue factor (TF) by up-regulating SOCS3 in RAW264.7 cells and HUVEC cells. Paeoniflorin promoted the release of Gas6 and activates the expression of p-Axl receptor. Our study provided an effective cure paeoniflorin to alleviate radiation enteritis, via activating Axl/SOCS3 axis and inhibiting the expression of p-ASK1 and TF.